Method for manufacturing nitride semiconductor light-emitting element and nitride semiconductor light-emitting element

JP2023135727A5Active Publication Date: 2025-02-21MEIJO UNIVERSITY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022040955
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-03-16
Publication Date
2025-02-21
Estimated Expiration
2042-03-16

AI Technical Summary

Technical Problem

Existing methods for manufacturing nitride semiconductor light-emitting devices face challenges such as high-density threading dislocations and surface pits due to threading dislocations and hydrogen treatment, which deteriorate surface flatness and hinder the formation of layers containing In.

Method used

A method involving metal organic vapor phase epitaxy (MOVPE) is used to grow a nitride semiconductor light-emitting device by laminating layers with a GaN cap layer followed by a hydrogen cleaning step to remove excess In, ensuring smooth crystal growth and reducing dislocations.

Benefits of technology

This approach results in a high-output, long-life nitride semiconductor light-emitting device with reduced pit density and improved surface flatness, enabling effective suppression of defects during crystal growth.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide a method for manufacturing a nitride semiconductor light-emitting element having good quality, and a nitride semiconductor light-emitting element having good quality.SOLUTION: A method for manufacturing a nitride semiconductor light-emitting element using an organic metal vapor deposition method includes: a first layer lamination step for crystal-growing an n-AlInN layer 12 containing Al and In in a composition; a cap layer lamination step for, after the first layer lamination step is performed, crystal-growing a GaN cap layer 13 containing Ga in a composition on the surface of the n-AlInN layer 12; and a second layer lamination step for, after the cap layer lamination step is performed, crystal-growing a GaN layer 14 containing Ga in a composition on the surface of the GaN cap layer 13. The method for manufacturing the nitride semiconductor light-emitting element further includes a hydrogen cleaning step for, after the cap layer lamination step is performed and before the second layer lamination step is performed, stopping the supply of raw material gas into a reaction furnace, and supplying hydrogen into the reaction furnace to clean at least the surface of the GaN cap layer 13.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for manufacturing a nitride semiconductor light-emitting device and a nitride semiconductor light-emitting device.

Background Art

[0002] When manufacturing a semiconductor multilayer film by laminating nitride semiconductor thin films having different band gaps and refractive indexes, particularly in a multilayer film mirror using a nitride semiconductor thin film containing In, the problem has been that defects such as threading dislocations exist at high density. In Patent Document 1, a method (hydrogen treatment) is disclosed in which by performing a step of introducing hydrogen immediately after forming an AlInN layer, clusters of In present on the surface of the AlInN layer are removed, and the generation of defects such as threading dislocations is suppressed. In Patent Document 2, it is disclosed that the reduction rate of the In composition at the interface between the upper part of the AlInN layer and the lower part of the GaN layer is made larger than the reduction rate of the Al composition, that is, by a structure in which a layer substantially lacking In exists at the interface between the AlInN layer and the GaN layer, the generation of defects such as threading dislocations is suppressed. Specifically, immediately after forming the AlInN layer, a cap layer containing no In and larger than 0 nm and 1 nm or less is formed, and then by performing a temperature-raising step of raising the substrate temperature, clusters of In present on the surface of the AlInN layer are removed, and the generation of defects is suppressed (temperature-raising treatment). Here, the cap layer includes not only a state in which the surface of the AlInN layer is evenly covered but also a state in which it is formed in an island shape on the surface of the AlInN layer.

Prior Art Documents

Patent Documents

[0003]

Patent Document 1

Patent Document 2

Summary of the Invention

Problems to be Solved by the Invention

[0004] Under these circumstances, several nitride semiconductor thin film multilayer structures were investigated for the purpose of forming device structures, and the following new challenges were identified. Specifically, this is the case when forming a structure having an In-containing layer on the surface of an AlInN layer. First, the aforementioned heating process involves a temperature increase, making it difficult to form a structure having an In-containing layer. On the other hand, it was newly discovered that the hydrogen treatment described above generates pits (holes) on the surface of the AlInN layer at a density significantly higher than the dislocation density of the substrate, greatly deteriorating the surface flatness. The pits are thought to have appeared on the crystal surface due to the presence of crystal defects such as through dislocations. Thus, it became clear that there are cases where the suppression of dislocation generation is insufficient with only the techniques disclosed in Patent Documents 1 and 2 (i.e., when crystal growth is essential while keeping the growth temperature low, or when growing a structure having an In-containing layer on the surface of an AlInN layer).

[0005] The present invention has been made in view of the above-mentioned conventional circumstances, and aims to provide a method for manufacturing a nitride semiconductor light-emitting element, and a nitride semiconductor light-emitting element, which involves growing crystals with a low pit density, i.e., few defects, on the surface of an AlInN layer to produce a high-power and long-life nitride semiconductor light-emitting element. [Means for solving the problem]

[0006] The first invention's method for manufacturing a nitride semiconductor light-emitting element is: A method for manufacturing a nitride semiconductor light-emitting element using metal-organic vapor deposition, A first layer lamination step involves growing a first layer containing Al and In in its composition, After performing the first layer lamination step, a cap layer lamination step is performed in which a cap layer containing Ga in its composition is crystallized on the surface of the first layer, After performing the cap layer lamination step, a second layer lamination step is performed in which a second layer containing at least one of the Ga and In in its composition is grown on the surface of the cap layer. Equipped with, The process further includes a hydrogen cleaning step, performed after the cap layer lamination step and before the second layer lamination step, in which the supply of raw material gas to the reactor is stopped and hydrogen is supplied to the reactor to clean at least the surface of the cap layer.

[0007] With this configuration, the crystal surface after the cap layer stacking process is cleaned with hydrogen, which allows for good crystal growth of the second layer that is stacked next.

[0008] The nitride semiconductor light-emitting device of the second invention is A first layer containing Al and In in its composition, A cap layer containing Ga is laminated on the surface of the first layer, A second layer laminated on the surface of the cap layer, comprising at least one of Ga and In in its composition, Equipped with, The band gap in the cap layer is smaller than the band gap in the region adjacent to the cap layer in the first and second layers.

[0009] With this configuration, the cap layer allows for good crystal growth of the second layer that is subsequently stacked. Furthermore, the Ga contained in the cap layer diffuses to some extent into the adjacent first and second layers, reducing the band offset in the cap layer, thus allowing for smoother electron movement in the cap layer. [Brief explanation of the drawing]

[0010] [Figure 1] This is a schematic diagram showing an example of the structure of a nitride semiconductor light-emitting element 1 manufactured by a nitride semiconductor light-emitting element manufacturing method. [Figure 2] This is a time chart showing the steps in the manufacturing method of nitride semiconductor light-emitting devices, from the first layer stacking step, the cap layer stacking step, the hydrogen cleaning step, the second layer stacking step, to the step of stacking the GaInN quantum well active layer. [Figure 3](A) to (H) are images of the surface of the GaInN quantum well active layer of each sample in which the thickness of the GaN cap layer was varied by changing the execution time of the cap layer lamination process, observed with an atomic force microscope. (I) is an image of the surface of the GaInN quantum well active layer of a sample prepared without performing the cap layer lamination process and the hydrogen cleaning process, observed with an atomic force microscope. [Figure 4] This graph plots the relationship between pit density and GaN cap layer thickness in each sample where the execution time of the cap layer lamination process was varied to change the thickness of the GaN cap layer. [Figure 5] This is a schematic diagram showing the structure of a nitride semiconductor light-emitting element 2 manufactured by a nitride semiconductor light-emitting element manufacturing method. [Figure 6] This table shows the flow rates of H2 and NH3 into the reactor, the supply time of H2 into the reactor, the numerical value A, and the pit density for each sample in which the ratio of H2 and NH3 supplied into the reactor and the supply time of H2 into the reactor were varied during the hydrogen cleaning process. [Figure 7] This graph plots the relationship between the pit density and the numerical value A for each sample in which the ratio of H2 and NH3 supplied to the reactor and the H2 supply time to the reactor were varied during the hydrogen cleaning process. [Figure 8] This is a schematic diagram showing the structure of the sample in Comparative Example 4. [Figure 9] This graph shows the depth profiles of Ga, Al, and In obtained by SIMS analysis in the sample of Comparative Example 4. [Figure 10] These are schematic diagrams showing the energy levels at the bottom of the valence band in the samples of Examples 7 to 10 and Comparative Example 7. [Figure 11] This graph shows the current-voltage characteristics of the samples from Comparative Example 7 and Example 9. [Modes for carrying out the invention]

[0011] Preferred embodiments of the present invention will be described.

[0012] In the first invention, the thickness of the cap layer in the stacking direction may be 0.3 nm or more and 5 nm or less. With this configuration, when the second layer is stacked in the second layer stacking process, dislocations that occur in the second layer can be effectively suppressed.

[0013] In the first invention, the numerical value A in Equation 1, which is determined by the flow rate F1 [slm] of hydrogen supplied into the reactor in the hydrogen cleaning process, the supply time T [min] for supplying hydrogen into the reactor in the hydrogen cleaning process, and the flow rate F2 [slm] of ammonia supplied into the reactor in the hydrogen cleaning process, may be 20 or more and 80 or less. A = (F1 × T) / F2 ... Equation 1 With this configuration, by adjusting the hydrogen flow rate F1 [slm] supplied to the reactor during the hydrogen cleaning process, the hydrogen supply time T [min] during the hydrogen cleaning process, and the ammonia flow rate F2 [slm] supplied to the reactor during the hydrogen cleaning process, the value A can be set within this range, thereby enhancing the hydrogen cleaning effect on the crystal surface after the cap layer lamination process. If the value A is too low, the cleaning effect will be lost, and if it is too high, surface damage due to hydrogen will begin to occur.

[0014] In the first invention, the growth temperature in the second layer lamination process may be lower than or equal to the growth temperature in the first layer lamination process. This configuration makes it possible to suppress the thermal effects on the first layer containing In.

[0015] In the second invention, the thickness of the cap layer in the stacking direction may be 0.3 nm or more and 5 nm or less. With this configuration, dislocations that occur in the second layer when stacking the second layer can be effectively suppressed.

[0016] In the second invention, the surface concentration of Ga in the cap layer is 2.5 × 10 14 cm -2 The above, and 4.1 × 10 15 cm-2 The following is possible. With this configuration, dislocations occurring in the second layer can be effectively suppressed when the second layer is stacked.

[0017] <Examples 1-6, Comparative Examples 1-4> Next, an example of a manufacturing method for the nitride semiconductor light-emitting element of the present invention will be described with reference to the drawings. This manufacturing method is an example of a manufacturing method for a light-emitting diode (hereinafter also referred to as nitride semiconductor light-emitting element 1) using an element structure in which a GaInN / GaN multiple quantum well active layer (light-emitting layer) is formed on the surface side of an AlInN layer via a GaN layer. This element structure can be used as the basic structure for various optical device structures other than light-emitting diodes, such as laser diodes and solar cells.

[0018] As shown in Figure 1, the nitride semiconductor light-emitting element 1 comprises an n-GaN substrate 10, an n-GaN buffer layer 11, a first layer, an n-AlInN layer 12, a cap layer, a GaN cap layer 13, a second layer, a GaN layer 14, a GaInN quantum well active layer 15, a p-AlGaN layer 16, a p-GaN layer 17, a p-GaN contact layer 18, a p-side electrode 19A, and an n-side electrode 19B. The n-GaN substrate 10 is a single crystal substrate of GaN (gallium nitride) having n-type properties. The nitride semiconductor light-emitting element 1 can be manufactured by epitaxial growth on the surface of the n-GaN substrate 10 (the upper surface in Figure 1) using metal-organic vapor phase epitaxy (MOVPE).

[0019] When manufacturing nitride semiconductor light-emitting element 1, TMA (trimethylaluminum), TMGa (trimethylgallium), TEGa (triethylgallium), and TMI (trimethylindium) are used as Group III materials (MO raw materials). Ammonia (NH3) is used as the raw material gas for Group V materials. SiH4 (silane) is used as the raw material gas for donor impurities. CP2Mg (cyclopentadienylmagnesium) is used as the MO raw material for acceptor impurities.

[0020] First, an n-GaN buffer layer 11 is grown on the surface of the n-GaN substrate 10 to a thickness of 500 nm as a buffer layer. Specifically, the n-GaN substrate 10 is placed inside the reaction furnace of the MOVPE apparatus (hereinafter also simply referred to as "inside the reaction furnace"). Then, the temperature inside the reaction furnace is adjusted so that the temperature of the n-GaN substrate 10 (growth temperature) is 1050°C, and hydrogen (H2) is supplied into the reaction furnace as a carrier gas. The concentration of Si (silicon) in the n-GaN buffer layer 11 is 5 × 10⁻¹⁶. 18 cm -3 The amount of SiH4 supplied into the reactor is adjusted to achieve this.

[0021] [First layer lamination process] Next, the first layer lamination process is performed. Specifically, an n-AlInN layer 12 containing Al and In in its composition is epitaxially grown on the surface of the n-GaN buffer layer 11. In detail, as shown in Figure 2, the temperature inside the reactor is adjusted so that the temperature of the n-GaN substrate 10 (growth temperature) is 840°C, and nitrogen (N2) is supplied to the reactor as a carrier gas. In addition, TMA, TMI, SiH4, and NH3 at a flow rate of 4 L / min are supplied to the reactor to crystallize an n-AlInN layer 12 with a thickness of 43 nm. The mole fraction of AlN in the n-AlInN layer 12 is 82%, and the mole fraction of InN is 18%. The concentration of Si in the n-AlInN layer 12 is 1.5 × 10⁻⁶. 19 cm -3 The amount of SiH4 supplied to the reactor is adjusted so that the desired result is achieved. The carrier gas may be an inert gas such as Ar (argon) or a mixture of these, in addition to N2.

[0022] [Cap layer lamination process] Next, after the first layer lamination process is performed, the cap layer lamination process is carried out. Specifically, as shown in Figure 2, while maintaining the temperature (growth temperature) of the n-GaN substrate 10, the supply of carrier gas (N2) and NH3 into the reactor, the supply of TMA, TMI, and SiH4 is stopped, and TEGa is supplied into the reactor to grow a GaN cap layer 13 containing Ga in its composition to a predetermined thickness on the surface of the n-AlInN layer 12. The thickness of the GaN cap layer 13 can be changed by changing the supply time of TEGa into the reactor.

[0023] [Hydrogen cleaning process] After stopping the supply of TEGa (raw material gas) to the reactor and terminating the crystal growth of the GaN cap layer 13, i.e., after the cap layer lamination process is performed, a hydrogen cleaning process is carried out. Specifically, as shown in Figure 2, the temperature of the n-GaN substrate 10 is maintained at the temperature during the cap layer lamination process (840°C), and the carrier gas supplied to the reactor at a flow rate of 16 L / min is gradually switched from N2 to H2. Specifically, while maintaining the flow rate of the carrier gas supplied to the reactor at 16 L / min, the proportion of N2 is decreased while the proportion of H2 is increased.

[0024] Here, if the hydrogen cleaning process is started and the supply of N2 to the reactor is stopped, and then the supply of H2 is immediately started, the gas flow in the reactor may be disturbed. For this reason, by gradually switching the carrier gas from N2 to H2 at the same time as the hydrogen cleaning process is started, the flow rate of the carrier gas supplied to the reactor is kept constant, thereby suppressing disturbance of the gas flow in the reactor. In principle, if there is no fluctuation in the flow rate of the carrier gas supplied to the reactor, the supply of H2 to the reactor may be started immediately after stopping the N2 supply at the same time as the hydrogen cleaning process is started. In the manufacturing method of the nitride semiconductor light-emitting element 1, the switch from N2 to H2 is completed over 1.5 minutes (see Figure 2). This operation starts the supply of H2 to the reactor, and the surface of the n-AlInN layer 12, which includes a thin GaN cap layer 13, can be cleaned with H2.

[0025] The state in which only H2 is supplied as a carrier gas into the reactor may be maintained for a desired period of time. However, in the manufacturing method of the nitride semiconductor light-emitting element 1, there is no time set aside to maintain the state in which only H2 is supplied as a carrier gas into the reactor. Instead, as soon as the carrier gas becomes only H2, the carrier gas is gradually switched from H2 to N2. Specifically, while maintaining the flow rate of the carrier gas supplied into the reactor at 16 L / min, the proportion of H2 is decreased while the proportion of N2 is increased over 1.5 minutes. In this way, H2 is gradually introduced into the reactor over 3 minutes, so the amount of H2 supplied into the reactor is (16 [L / min] × 3 [min]) ÷ 2 = 24 [L], which is essentially equivalent to supplying 16 slm of H2 into the reactor for 1.5 minutes. Thus, the hydrogen cleaning process cleans the surface of the GaN cap layer 13 by supplying hydrogen into the reactor. In this case, if the GaN cap layer 13 is formed in an island-like manner on the surface of the n-AlInN layer 12, the hydrogen cleaning process involves supplying hydrogen into the reactor to clean the surfaces of the GaN cap layer 13 and the n-AlInN layer 12.

[0026] [Second layer lamination process] Next, the second layer lamination process is performed. Specifically, as shown in Figure 2, after the cap layer lamination process and the hydrogen cleaning process are performed, the temperature of the n-GaN substrate 10 is lowered from the temperature used for crystal growth of the n-AlInN layer 12 (840°C) to 797°C. While maintaining the state of N2 as the carrier gas, the supply of TEGa to the reactor is started, and a GaN layer 14 with a thickness of 30 nm is crystallized on the surface of the GaN cap layer 13. The GaN layer 14 contains Ga in its composition. The growth temperature in the second layer lamination process is lower than the growth temperature in the first layer lamination process. The hydrogen cleaning process is performed before the second layer lamination process is performed.

[0027] Subsequently, while maintaining the supply of NH3 and TEGa into the reactor, the GaInN quantum well active layer 15 (MQW) is grown. Specifically, after starting the supply of TMIn into the reactor and crystal-growing a GaInN quantum well layer with a thickness of 3 nm, the supply of TMIn is stopped and a GaN barrier layer with a thickness of 6 nm is crystal-grown. The GaInN quantum well active layer 15 has a structure in which one pair consists of one GaInN quantum well layer and one GaN barrier layer, and five pairs of this are stacked. After the crystal growth of the last GaN barrier layer is completed, the supply of TEGa into the reactor is stopped, and the crystal growth of the GaInN quantum well active layer 15 is completed.

[0028] [Verification of the Effects of the GaN Cap Layer and the Hydrogen Cleaning Process] Here, in order to verify the effects of the GaN cap layer 13 and the hydrogen cleaning process, a total of eight types of samples from Example 1 to Example 5 and Comparative Example 1 to Comparative Example 3 were prepared by changing the thickness of the GaN cap layer 13 and crystal-growing up to the GaInN quantum well active layer 15. Specifically, the thickness of the GaN cap layer 13 of each of these samples was 0 nm (Comparative Example 1), 0.15 nm (Comparative Example 2), 0.3 nm (Example 1), 0.6 nm (Example 2), 0.9 nm (Example 3), 1.2 nm (Example 4), 2.4 nm (Example 5), 5 nm (Example 6). The thickness of the GaN cap layer 13 in each sample was adjusted by changing the time for performing the cap layer stacking process, that is, the supply time of TEGa into the reactor. Furthermore, a sample of Comparative Example 3 was also prepared in which the GaInN quantum well active layer 15 was crystal-grown without performing the cap layer stacking process and the hydrogen cleaning process.

[0029] In the sample of Comparative Example 3, the pit density on the surface of the GaInN quantum well active layer 15 was 1.5×10 7 cm -3 (see Fig. 3(I)). Here, the guaranteed value of the dislocation density of the n-GaN substrate 10 is 1×10 6 cm -3Therefore, it is thought that the bonding of excess In atoms on the surface of the n-AlInN layer 12 is the cause of dislocation generation at a density exceeding that of the n-GaN substrate 10.

[0030] Furthermore, even in the sample of Comparative Example 1, where the cap layer lamination process was not performed (there was no GaN cap layer 13 at all (0 nm)) and the hydrogen cleaning process was performed, the pit density on the surface of the GaInN quantum well active layer 15 was 8.8 × 10⁻⁶. 8 cm -3 This is the result (see Figures 3(A) and 4). In other words, it was found that the pit density on the surface of the GaInN quantum well active layer 15 is significantly higher when the cap layer lamination process is not performed but the hydrogen cleaning process is performed compared to when neither the cap layer lamination process nor the hydrogen cleaning process is performed.

[0031] Furthermore, it was found that the sample from Comparative Example 2, in which the GaN cap layer 13 had a thickness of 0.15 nm, also had a higher pit density (dislocation density) than the sample without the hydrogen cleaning process (Comparative Example 3) (see Figures 3(B) and 4). On the other hand, it was found that the lowest pit density was obtained when the GaN cap layer 13 had a thickness of 0.6 nm (Example 2) (see Figures 3(D) and 4). It was also found that the dislocation density could be effectively reduced by the hydrogen cleaning process when the thickness was greater than or equal to half of this thickness (0.6 nm) (0.3 nm) (Example 1) and 8.3 times (5 nm) (Example 6) the thickness.

[0032] Specifically, when the thickness of the GaN cap layer 13 is 0.3 nm or more and 5.0 nm or less, the pit density is 6.3 × 10⁻⁶. 6 cm -3 The following applies. In other words, the thickness of the GaN cap layer 13 in the stacking direction is preferably 0.3 nm or more and 5 nm. Also, when the thickness of the GaN cap layer 13 is 0.6 nm (Example 2) or more and 1.2 nm (Example 4) or less, the pit density is 5 × 10⁻¹⁶. 6 cm -3The following values ​​were found to be more favorable. Furthermore, when the thickness of the GaN cap layer 13 is 0.6 nm (Example 2) or more and 0.9 nm (Example 3) or less, the pit density is 2.3 × 10⁻⁶. 6 cm -3 The following values ​​were observed, and it was also found that even more favorable values ​​were observed. Therefore, the thickness of the GaN cap layer 13 is more preferably 0.6 nm or more and 1.2 nm or less, and even more preferably 0.6 nm or more and 0.9 nm or less. Thus, the effect of the hydrogen cleaning process is to suppress the pit density on the surface of the stacked crystals.

[0033] Here, we investigated how much Ga is present when a 0.6 nm thick GaN cap layer 13 is crystallized in the sample of Example 2. Specifically, a sample of Comparative Example 4, as shown in Figure 8, was prepared separately. More specifically, in the sample of Comparative Example 4, similar to the sample of Example 2, a GaN cap layer 13 with a thickness of 0.6 nm was formed on the surface of an n-AlInN layer 12 with a thickness of 43 nm, and then a hydrogen cleaning process was performed. Then, an AlInN layer 44 with a thickness of 10 nm was crystallized on the surface of the GaN cap layer 13. In the sample of Example 2, a GaN layer 14 was crystallized on the surface of the GaN cap layer 13, but here, in order to determine how much Ga is present in the GaN cap layer 13, an AlInN layer 44 that does not contain Ga was also crystallized on top of the sample of Comparative Example 4.

[0034] Figure 9 shows the depth profiles of Ga, Al, and In obtained by SIMS analysis in the sample of Comparative Example 4. As shown in Figure 9, the peak value of the volume concentration of Ga is approximately 3 × 10⁻⁶. 21 cm -3 The Ga volume concentration profile had a full width at half maximum of approximately 2 nm. Based on this profile, the surface concentration of Ga was calculated to be 4.9 × 10⁻⁶. 14 cm -2 That is, as described above, when a 0.6 nm GaN cap layer 13 is provided, there is 4.9 × 10 between the n-AlInN layer 12 and the AlInN layer 44. 14 cm -2It was found that Ga is present at a surface concentration of 10⁻¹⁵. This surface concentration of Ga changes accordingly when the thickness of the GaN cap layer 13 is changed. Specifically, when the thickness of the GaN cap layer 13 is 0.3 nm (Example 1), the surface concentration of Ga is 2.5 × 10⁻¹⁵. 14 cm -2 Therefore, when the thickness of the GaN cap layer 13 is 0.9 nm (Example 3), the surface concentration of Ga is 7.4 × 10⁻⁶. 14 cm -2 Therefore, when the thickness of the GaN cap layer 13 is 1.2 nm (Example 4), the surface concentration of Ga is 9.8 × 10⁻⁶. 14 cm -2 Therefore, when the thickness of the GaN cap layer 13 is 5 nm (Example 6), the surface concentration of Ga is 4.1 × 10⁻⁶. 15 cm -2 It was found that this is the case.

[0035] Therefore, when laminating a structure (GaInN quantum well active layer 15) having at least a layer containing Ga (GaN layer 14) and an In layer on the surface of a layer containing at least Al and In (n-AlInN layer 12), a GaN cap layer 13 with a thickness of 0.3 nm or more and 5 nm or less is provided, and a hydrogen cleaning process is performed to bring the surface concentration of Ga in the GaN cap layer 13 to 2.5 × 10⁻⁶. 14 cm -2 The above, and 4.1 × 10 15 cm -2 It was found that the generation of pits and dislocations can be significantly suppressed by doing the following.

[0036] After performing the first layer stacking process to grow an n-AlInN layer 12, a cap layer stacking process, a hydrogen cleaning process, and a second layer stacking process are performed to further grow a GaInN quantum well active layer 15. Then, a p-AlGaN layer 16, a p-GaN layer 17, a p-GaN contact layer 18, a p-side electrode 19A, and an n-side electrode 19B are grown to fabricate a light-emitting diode (nitride semiconductor light-emitting element 1).

[0037] Specifically, after growing the GaInN quantum well active layer 15, the following crystal growth is carried out. First, a p-AlGaN layer 16 with a thickness of 20 nm is grown on the surface of the GaInN quantum well active layer 15. The mole fraction of AlN in the p-AlGaN layer 16 is 20%, and the mole fraction of GaN is 80%. The concentration of Mg in the p-AlGaN layer 16 is 2 × 10⁻⁶. 19 cm -3 The amount of CP2Mg supplied into the reactor is adjusted to achieve this.

[0038] Next, a p-GaN layer 17 with a thickness of 70 nm is crystallized on the surface of the p-AlGaN layer 16 as a p-type cladding layer. The Mg concentration in the p-GaN layer 17 is 2 × 10⁻⁶ 19 cm -3 The amount of CP2Mg supplied into the reactor is adjusted so that the following occurs. Next, a p-GaN contact layer 18 with a thickness of 10 nm is grown on the surface of the p-GaN layer 17. The Mg concentration in the p-GaN contact layer 18 is 2 × 10⁻⁶. 20 cm -3 The amount of Cp2Mg supplied into the reactor is adjusted so that the following occurs. Then, an n-side electrode 19B is provided on the back surface of the n-GaN substrate 10, an ITO electrode (p-side electrode 19A) is provided on the surface of the p-GaN contact layer 18, and a metal pad electrode (not shown) is provided. In this way, a nitride semiconductor light-emitting element 1 that functions as a light-emitting diode is completed.

[0039] Next, the operation in the above embodiment will be explained.

[0040] A method for manufacturing a nitride semiconductor light-emitting element using metal-organic vapor deposition (CMD) comprises: a first layer stacking step of growing an n-AlInN layer 12 containing Al and In in its composition; a cap layer stacking step of growing a GaN cap layer 13 containing Ga in its composition on the surface of the n-AlInN layer 12 after the first layer stacking step; and a second layer stacking step of growing a GaN layer 14 containing Ga in its composition on the surface of the GaN cap layer 13 after the cap layer stacking step. This method for manufacturing a nitride semiconductor light-emitting element further comprises a hydrogen cleaning step of stopping the supply of raw material gas to the reactor and supplying hydrogen to the reactor to clean the surfaces of the GaN cap layer 13 and the n-AlInN layer 12 after the cap layer stacking step and before the second layer stacking step. With this configuration, the excess In present on the surface of the crystal after the cap layer stacking step can be cleaned with hydrogen, thereby enabling good crystal growth of the next stacked GaN layer 14. Therefore, this method for manufacturing nitride semiconductor light-emitting elements can sufficiently suppress the occurrence of defects such as pits, i.e., dislocations, making it possible to produce light-emitting diodes (nitride semiconductor light-emitting elements 1) with high efficiency, high output, and long lifespan.

[0041] In this nitride semiconductor light-emitting device manufacturing method, the thickness of the GaN cap layer 13 in the stacking direction is 0.3 nm or more and 5 nm or less. With this configuration, when the GaN layer 14 is stacked in the second layer stacking process, dislocations occurring in the GaN layer 14 can be effectively suppressed.

[0042] In this nitride semiconductor light-emitting device manufacturing method, when a GaN cap layer 13 is provided and a hydrogen cleaning process is performed, the Ga surface concentration of the GaN cap layer 13 is 2.5 × 10 14 cm -2 The above, and 4.1 × 10 15 cm -2 The following is the result. With this configuration, when the GaN layer 14 is stacked in the second layer stacking process, dislocations that occur in the GaN layer 14 can be effectively suppressed.

[0043] In this nitride semiconductor light-emitting device manufacturing method, the growth temperature in the second layer stacking process is lower than or equal to the growth temperature in the first layer stacking process. This configuration makes it possible to suppress the influence of heat on the in-containing n-AlInN layer 12.

[0044] In the nitride semiconductor light-emitting element 1, the thickness of the GaN cap layer 13 in the stacking direction is 0.3 nm or more and 5 nm or less. With this configuration, dislocations that occur in the GaN layer 14 when stacking the GaN layer 14 can be effectively suppressed.

[0045] In the nitride semiconductor light-emitting element 1, the surface concentration of Ga in the GaN cap layer 13 is 2.5 × 10⁻⁶. 14 cm -2 The above, and 4.1 × 10 15 cm -2 The following is the result. With this configuration, dislocations that occur in the GaN layer 14 when stacking the GaN layer 14 can be effectively suppressed.

[0046] <Examples 7-10, Comparative Examples 5-7> Next, another example illustrating the method for manufacturing a nitride semiconductor light-emitting element of the present invention will be described with reference to the drawings. This manufacturing method is an example of forming an n-type AlInN / GaN multilayer reflector structure having an AlGaInN composition gradient layer 114 on the surface side of an n-AlInN layer 112, and manufacturing a surface-emitting laser (hereinafter also referred to as nitride semiconductor light-emitting element 2) using this structure. The n-type AlInN / GaN multilayer reflector structure can be used not only in surface-emitting lasers but also in various optical device structures such as light-emitting diodes and solar cells. A schematic cross-sectional view of an example of the structure of a surface-emitting laser (nitride semiconductor light-emitting element 2) using this structure is shown in Figure 5.

[0047] As shown in Figure 5, the nitride semiconductor light-emitting element 2 comprises an n-GaN substrate 110, an n-GaN buffer layer 111, a first n-AlInN layer 112, a GaN cap layer 113, a second n-AlGaInN composition gradient layer 114, a first n-GaN layer 115, a second n-GaN layer 116, a GaInN quantum well active layer 117, a p-AlGaN layer 118, a p-GaN layer 119, a p-GaN contact layer 120, a p-side electrode 122A, and an n-side electrode 122B. The n-GaN substrate 110 is a single crystal substrate of GaN having n-type properties. The nitride semiconductor light-emitting element 2 can be manufactured by epitaxial growth on the surface of the n-GaN substrate 110 (the upper surface in Figure 5) using metal-organic vapor deposition.

[0048] When manufacturing nitride semiconductor light-emitting devices 2, TMA, TMGa, TEGa, and TMI are used as Group III materials (MO raw materials). NH3 is used as the raw material gas for Group V materials. SiH4 is used as the raw material gas for donor impurities. CP2Mg is used as the MO raw material for acceptor impurities.

[0049] First, an n-GaN buffer layer 111 is grown on the surface of the n-GaN substrate 110 to a thickness of 500 nm as a buffer layer. Specifically, the n-GaN substrate 110 is placed in the reaction furnace of the MOVPE apparatus. Then, the temperature inside the reaction furnace is adjusted so that the temperature of the n-GaN substrate 110 (growth temperature) is 1050°C, and H2 is supplied to the reaction furnace as a carrier gas. The Si concentration in the n-GaN buffer layer 111 is 5 × 10⁻¹⁶. 18 cm -3 The amount of SiH4 supplied into the reactor is adjusted to achieve this.

[0050] [First layer lamination process] Next, the first layer lamination process is performed. Specifically, an n-AlInN layer 112 is epitaxially grown on the surface of the n-GaN buffer layer 111. More specifically, the temperature inside the reactor is adjusted so that the temperature of the n-GaN substrate 110 (growth temperature) is 840°C, and N2 is supplied to the reactor as a carrier gas. In addition, TMA, TMI, SiH4, and NH3 are supplied to the reactor to grow a 38 nm thick n-AlInN layer 112. The mole fraction of AlN in the n-AlInN layer 112 is 82%, and the mole fraction of InN is 18%. The Si concentration in the n-AlInN layer 112 is 1.5 × 10⁻⁶. 19 cm -3 The amount of SiH4 supplied to the reactor is adjusted so that the desired result is achieved. The carrier gas may be an inert gas other than N2, such as Ar or Ne (neon), or a mixed gas of these.

[0051] [Cap layer lamination process] Next, the cap layer lamination process is performed. Specifically, while maintaining the temperature (growth temperature) of the n-GaN substrate 110, the supply of carrier gas (N2) and NH3 into the reactor, the supply of TMA, TMI, and SiH4 is stopped, and TEGa is supplied into the reactor to grow a GaN cap layer 113 on the surface of the n-AlInN layer 112. The thickness of the GaN cap layer 113 is set to 0.3 nm.

[0052] [Hydrogen cleaning process] After stopping the supply of TEGa to the reactor and terminating the crystal growth of the GaN cap layer 113, a hydrogen cleaning process is performed. Specifically, the temperature of the n-GaN substrate 110 (growth temperature) is maintained at the temperature used in the cap layer lamination process (840°C), and the carrier gas supplied to the reactor is gradually switched from N2 to H2. The supply of NH3 to the reactor is maintained. More specifically, while maintaining the flow rate of the carrier gas supplied to the reactor at a predetermined flow rate, the proportion of H2 is increased while the proportion of N2 is decreased, and the switch from N2 to H2 is performed over 30 seconds. This operation starts the supply of H2 to the reactor, allowing the surface of the n-AlInN layer 112, including the thin GaN cap layer 113, to be cleaned by H2. Then, the state in which only H2 is supplied as the carrier gas to the reactor is maintained for a predetermined time. After that, the carrier gas is gradually switched from H2 to N2. Specifically, while maintaining the flow rate of the carrier gas supplied into the reactor at a predetermined rate, the proportion of H2 is decreased while the proportion of N2 is increased, and the carrier gas is switched from H2 to N2 over 30 seconds.

[0053] [Second layer lamination process] After performing the cap layer lamination process and the hydrogen cleaning process, the second layer lamination process is performed. Specifically, while maintaining the growth temperature at the temperature used for crystal growth of the n-AlInN layer 112 (840°C), and with N2 as the carrier gas, an n-AlGaInN composition gradient layer 114 containing Al and In and having a thickness of 5 nm is crystallized. The n-AlGaInN composition gradient layer 114 is crystallized in the following manner. The growth temperature in the second layer lamination process is the same as the growth temperature in the first layer lamination process.

[0054] First, crystal growth is initiated using the same supply of TMA and TMI as when growing the n-AlInN layer 112, and the supply of TMA and TMI to the reactor is gradually reduced. Simultaneously, the supply of TEGa, which was not supplied immediately after the start of the second layer stacking process, is started and the supply of TEGa is gradually increased. Finally, the supply of TMA and TMI to the reactor is stopped, and the supply of TEGa is gradually increased to approximately the same rate as the growth rate of the n-AlInN layer 112. This causes the composition to change in the stacking direction from the n-AlInN layer 112 to the first n-GaN layer 115, resulting in the crystal growth of an n-AlGaInN composition gradient layer 114 with a thickness of 5 nm. Furthermore, in order to obtain n-type properties, the Si concentration in the n-AlGaInN composition gradient layer 114 is set to 6 × 10⁻⁶. 19 cm -3 The amount of SiH4 supplied into the reactor is adjusted to achieve this.

[0055] After stopping the supply of TMA, TMI, TEGa, and SiH4 and terminating the crystal growth of the 5nm n-AlGaInN composition gradient layer 114, the temperature of the n-GaN substrate 110 (growth temperature) is raised to 1050°C, the growth temperature of the first n-GaN layer 115, while maintaining the supply of NH3 into the reactor. At this time, since the supply of TMA, TMI, TEGa, and SiH4 into the reactor has been stopped, crystal growth is interrupted. Then, while crystal growth is interrupted, the carrier gas is gradually switched from N2 to H2.

[0056] Then, after the temperature of the n-GaN substrate 110 reaches 1050°C, the supply of TMGa into the reactor is started, and a first n-GaN layer 115 with a thickness of 43 nm is grown. The Si concentration in the first n-GaN layer 115 is 5 × 10⁻⁶. 18 cm -3 The amount of SiH4 supplied into the reactor is adjusted so that the following occurs. The n-AlInN layer 112, the GaN cap layer 113, the n-AlGaInN composition gradient layer 114, and the first n-GaN layer 115 correspond to one pair P of the multilayer reflector structure.

[0057] After growing the first n-GaN layer 115, the supply of TMGa to the reactor is stopped to interrupt crystal growth in order to grow the n-AlInN layer 112 again on the surface of the first n-GaN layer 115 (i.e., to repeatedly grow pairs P). While crystal growth is interrupted, the temperature of the n-GaN substrate 110 is lowered from 1050°C to 840°C. At this time, the carrier gas is gradually switched from H2 to N2. In this way, one pair P of the multilayer reflector structure (n-AlInN layer 112, GaN cap layer 113, n-AlGaInN composition gradient layer 114, and the first n-GaN layer 115) is grown 40 times, thereby growing an n-AlInN / GaN multilayer reflector M in which 40 pairs P are stacked.

[0058] [Verification of the ratio of H2 and NH3 supplied to the reactor in the hydrogen cleaning process] Here, the effect of the hydrogen cleaning process (i.e., suppressing the pit density on the surface of the stacked crystals) is considered to be proportional to the flow rate of H2 supplied into the reactor during the hydrogen cleaning process (hereinafter also simply referred to as the H2 flow rate) and the supply time for which H2 is supplied into the reactor during the hydrogen cleaning process. On the other hand, NH3 is supplied into the reactor to protect the surface of the crystals during the hydrogen cleaning process, but if the effect of protecting the surface of the crystals is too strong (i.e., if the flow rate of NH3 into the reactor during the hydrogen cleaning process (hereinafter also simply referred to as the NH3 flow rate) is too high), the effect of removing In will be diminished. Therefore, the effect of the hydrogen cleaning process is considered to be inversely proportional to the NH3 flow rate. Hence, if we let the effect of this hydrogen cleaning process be represented by a numerical value A (hereinafter also simply referred to as numerical value A), and quantify this numerical value A with respect to the H2 flow rate F1 [slm], the H2 supply time into the reactor T [min], and the NH3 flow rate F2 [slm], then numerical value A can be expressed by the following equation.

[0059]

number

[0060] If this value A is too small, unnecessary In present on the surface of the n-AlInN layer 112 cannot be sufficiently removed, and if it is too large, it can lead to deterioration of the surface flatness of the n-AlInN layer 112 and the generation of new dislocations. Therefore, it is thought that value A provides an appropriate effect (suppression of pit density on the surface of the stacked crystals) within a predetermined numerical range.

[0061] To understand the relationship between the numerical value A and this effect, six types of samples were prepared: Examples 7-10 and Comparative Examples 5 and 6. These samples were created by crystallizing an n-GaN buffer layer 111 on the surface of an n-GaN substrate 110, and then repeating pair P 10 times to grow the crystals. Specifically, in these samples, the H2 flow rate F1 was kept constant (31 [slm]), and the H2 supply time T into the reactor and the NH3 flow rate F2 were varied.

[0062] As shown in Figure 6, the sample of Comparative Example 5 has a numerical value A of 12, and the pit density (hereinafter also simply referred to as pit density) of the surface where 10 pairs P are stacked is 1.6 × 10 6 cm -2 The sample in Example 7 had a numerical value A of 23 and a pit density of 8.3 × 10⁻⁶. 5 cm -2 The sample in Example 8 had a numerical value A of 23 and a pit density of 4.2 × 10⁻⁶. 5 cm -2 The sample in Example 9 had a numerical value A of 58 and a pit density of 1.5 × 10⁻⁶. 5 cm -2 The sample in Example 10 had a numerical value A of 72 and a pit density of 1.3 × 10⁻⁶. 5 cm -2 The results showed that the effect became more pronounced the more the hydrogen cleaning process was performed until the numerical value A reached 72. On the other hand, the sample in Comparative Example 6 had a numerical value A of 93 and a pit density of 4.4 × 10⁻⁶. 6 cm -2 The trend then shifted to an increasing one. In other words, as shown in Figure 7, it was found that when the value A exceeds approximately 80, the disadvantage of increased pit density outweighs the benefits obtained from the hydrogen cleaning process.

[0063] As shown in Figure 7, when the numerical value A exceeds 20, the pit density is equal to the guaranteed value of the dislocation density of the n-GaN substrate 110 (1 × 10⁻¹⁰). 6 cm -3 It was found that the value becomes less than or equal to ). On the other hand, when the value A exceeds 80, the pit density becomes 1 × 10 6 cm -3 It was also found that the value approached this range and even exceeded it. In other words, it was found that there is an appropriate range of numerical value A (20 to 80) for effectively reducing the pit density on the surface of the n-AlInN / GaN multilayer reflecting mirror M in which multiple pairs P are stacked. In this verification, a sample was used in which pairs P were repeated 10 times for crystal growth, but it is thought that even if the number of stacked pairs P is 11 or more, setting the numerical value A within this range (20 to 80) can effectively suppress the pit density on the surface of the stacked crystal. In other words, by setting the numerical value A, which is determined by the H2 flow rate F1 [slm], the H2 supply time T [min] into the reactor, and the NH3 flow rate F2 [slm], to a value between 20 and 80, it is possible to effectively reduce the pit density on the surface of the n-AlInN / GaN multilayer reflecting mirror M in which multiple pairs P are stacked.

[0064] Incidentally, the reason for providing an n-AlGaInN composition gradient layer 114 between the n-AlInN layer 112 and the first n-GaN layer 115 is, as shown in Figure 10(A), to substantially eliminate the band offset at the bottom of the valence band formed between the n-AlInN layer 112 and the first n-GaN layer 115, thereby eliminating the potential barrier formed at the heterointerface and making electron movement smoother (i.e., reducing resistance). On the other hand, in Examples 7 to 10, a GaN cap layer 113 is provided between the n-AlInN layer 112 and the n-AlGaInN composition gradient layer 114, which theoretically results in a large offset in the energy levels at the bottom of the valence band, as shown in Figure 10(B). If the GaN cap layer 113 is sufficiently thin, this effect is not significant, but as the number of pairs P increases, there was a concern that this effect would accumulate and increase resistance.

[0065] Therefore, as Comparative Example 7, an n-AlInN / GaN multilayer reflector was formed by repeating the n-AlInN layer 112, the n-AlGaInN composition gradient layer 114, and the first n-GaN layer 115 10 times without providing the GaN cap layer 113 and without performing the hydrogen cleaning process, and its current-voltage characteristics were measured. For comparison, the current-voltage characteristics of the sample from Example 9 were also measured. These results are shown in Figure 11. As shown in Figure 11, it became clear that even with the GaN cap layer 113, the current-voltage characteristics did not deteriorate significantly compared to the current-voltage characteristics in Example 9. This is because the actual GaN cap layer 113 does not have a structure with a steep interface as shown in Figure 10(B), but rather, as can be seen from the SIMS results in Figure 9, Ga is diffused to some extent into the adjacent layers above and below (i.e., the n-AlInN layer 112 and the n-AlGaInN composition gradient layer 114), and as a result the band offset in the GaN cap layer 113 is reduced and the structure changes more smoothly (Figure 10(C)). On the other hand, as the Ga profile in Figure 9 shows, Ga is still concentrated between the n-AlInN layer 112 and the n-AlGaInN composition gradient layer 114, and its concentration is higher than in the surrounding areas (n-AlInN layer 112 and n-AlGaInN composition gradient layer 114). In other words, in the nitride semiconductor light-emitting element 2, the band gap in the GaN cap layer 113 is smaller than the band gap in the regions adjacent to the GaN cap layer 113 in the n-AlInN layer 112 and the n-AlGaInN composition gradient layer 114, i.e., regions with low Ga concentration. Thus, it has become clear that the present invention can satisfy the requirements of both structural properties, such as surface flatness, and electrical properties.

[0066] After forming an n-AlInN / GaN multilayer reflecting mirror M by repeating pair P 40 times for crystal growth, a second n-GaN layer 116 with a thickness of 400 nm is crystal grown on the surface of the n-AlInN / GaN multilayer reflecting mirror M at a growth temperature of 1050°C. The Si concentration in the second n-GaN layer 116 is 5 × 10⁻⁶. 18 cm -3 The amount of SiH4 supplied into the reactor is adjusted to achieve this.

[0067] Next, a GaInN quantum well active layer 117 is grown on the surface of the second n-GaN layer 116, consisting of five stacks of a pair of GaInN quantum well layers and a GaN barrier layer. Then, a p-AlGaN layer 118 with a thickness of 20 nm is crystallized on the surface of the GaInN quantum well active layer 117. The mole fraction of AlN in the p-AlGaN layer 118 is 20%, and the mole fraction of GaN is 80%. The concentration of Mg in the p-AlGaN layer 118 is 2 × 10⁻⁶. 19 cm -3 Adjust the supply amount of Cp2Mg to achieve this.

[0068] Next, a p-GaN layer 119 with a thickness of 70 nm is grown as a p-type cladding layer on the surface of the p-AlGaN layer 118. The Mg concentration in the p-GaN layer 119 is 2 × 10⁻⁶. 19 cm -3 The supply amount of Cp2Mg is adjusted so that the following occurs. Then, the p-GaN contact layer 120 is grown on the surface of the p-GaN layer 119. The concentration of Mg in the p-GaN contact layer 120 is 2 × 10⁻⁶. 20 cm -3 Adjust the supply amount of Cp2Mg to achieve this.

[0069] Thus, a resonator structure is formed that includes an n-AlInN / GaN multilayer mirror M, which is formed by repeatedly growing a pair P 40 times, each having a high-quality layer (n-AlGaInN composition gradient layer 114) containing at least Ga and In on the surface of a layer (n-AlInN layer 112) containing at least Al and In, and a GaInN quantum well active layer 117 sandwiched between pn junctions that emits light in the purple region. This resonator has an integer multiple of the emission wavelength, and the resonator length corresponds to 4 wavelengths.

[0070] As shown in Figure 5, a surface-emitting laser is completed by growing an insulating film 121, a p-side electrode 122A, an n-side electrode 122B, and an SiO2 / Nb2O5 dielectric multilayer mirror D on a wafer having an n-AlInN / GaN multilayer mirror M and a resonator structure. The following describes the process of fabricating a surface-emitting laser (nitride semiconductor light-emitting element 2) by growing the insulating film 121, the p-side electrode 122A, the n-side electrode 122B, and the SiO2 / Nb2O5 dielectric multilayer mirror D.

[0071] First, the p-GaN contact layer 120 is grown in crystal form, and then H2 is removed from the p-type semiconductor layers (p-AlGaN layer 118, p-GaN layer 119, p-GaN contact layer 120) of the semiconductor wafer to activate the Mg p-type dopant added to the p-type semiconductor layer. Next, a pattern is formed on the surface of the semiconductor wafer using photoresist, and a mesa structure with a circular shape of 40 μm in diameter is formed by partial etching to create the device.

[0072] Then, a 20 nm thick SiO2 film is laminated onto the surface of the p-GaN contact layer 120, and an insulating film 121 with a circular opening H of 10 μm in diameter is formed by photolithography and sputtering. A transparent p-side electrode 122A made of ITO is then formed by sputtering so as to contact the surface of the p-GaN contact layer 120 exposed through the opening H. At the same time, an n-side electrode 122B is provided on the back surface of the n-GaN substrate 110. A pad electrode made of Cr / Ni / Au is then formed on the outer periphery of the surface of the p-side electrode 122A (not shown).

[0073] Finally, a SiO2 / Nb2O5 dielectric multilayer reflector D is grown on the surface of the p-side electrode 122A using photolithography and sputtering. In this way, a nitride semiconductor light-emitting element 2 is completed, which has a SiO2 / Nb2O5 dielectric multilayer reflector D above the GaInN quantum well active layer 117 and an n-AlInN / GaN multilayer reflector M below it, and functions as a vertical cavity surface-emitting laser with a cavity length corresponding to an integer multiple of the wavelength.

[0074] In this nitride semiconductor light-emitting device manufacturing method, the value A in Equation 1, which is determined by the flow rate F1 [slm] of hydrogen supplied into the reactor during the hydrogen cleaning process, the supply time T [min] for supplying hydrogen into the reactor during the hydrogen cleaning process, and the flow rate F2 [slm] of ammonia supplied into the reactor during the hydrogen cleaning process, is 20 or more and 80 or less. A = (F1 × T) / F2 ... Equation 1 With this configuration, by adjusting the flow rate F1 [slm] of hydrogen supplied into the reactor during the hydrogen cleaning process, the supply time T [min] for supplying hydrogen into the reactor during the hydrogen cleaning process, and the flow rate F2 [slm] of ammonia supplied into the reactor during the hydrogen cleaning process, the effect of hydrogen cleaning on the crystal surface after the cap layer lamination process can be enhanced.

[0075] The nitride semiconductor light-emitting element 2 comprises an n-AlInN layer 112 containing Al and In, a GaN cap layer 113 containing Ga and laminated on the surface of the n-AlInN layer 112, and an n-AlGaInN composition gradient layer 114 containing Ga and In and laminated on the surface of the GaN cap layer 113, wherein the band gap in the GaN cap layer 113 is smaller than the band gap in the regions adjacent to the GaN cap layer 113 in the n-AlInN layer 112 and the n-AlGaInN composition gradient layer 114.

[0076] With this configuration, the GaN cap layer 113 allows for good crystal growth of the subsequently stacked n-AlGaInN composition gradient layer 114. Furthermore, the Ga contained in the GaN cap layer 113 diffuses to some extent into the adjacent n-AlInN layer 112 and n-AlGaInN composition gradient layer 114, reducing the band offset in the GaN cap layer 113, thereby facilitating smooth electron movement in the GaN cap layer 113.

[0077] The embodiments disclosed herein should be considered in all respects to be illustrative and not restrictive. The scope of the present invention is not limited to the embodiments disclosed herein, but is indicated by the claims, and all modifications within the meaning and scope equivalent to the claims are intended to be included. (1) Unlike the above examples, Ge, Te, etc. may be used as n-type impurities. Also, Mg, Zn, Be, Ca, Sr, and Ba, etc. may be used as p-type impurities. (2) Unlike the above embodiment, crystal growth may be carried out using other substrates such as a sapphire substrate. (3) Unlike the above embodiment, in the second layer lamination process, a layer containing only In in its composition may be grown as a crystal. (4) Unlike the above examples, the GaN cap layer may contain elements other than GaN. (5) Unlike the above embodiment, the flow rate or supply time of H2 may be changed to adjust the value A. [Explanation of Symbols]

[0078] 1,2…Nitride semiconductor light-emitting element 12,112…n-AlInN layer (1st layer) 13,113…GaN capping layer (capping layer) 14…GaN layer (second layer) 114...n-AlGaInN composition gradient layer (second layer) A...numerical value F1...Flow rate of hydrogen supplied into the reactor during the hydrogen cleaning process. F2...Flow rate of ammonia supplied into the reactor during the hydrogen cleaning process. T... Supply time for supplying hydrogen into the reactor during the hydrogen cleaning process.

Claims

1. A method for manufacturing a nitride semiconductor light-emitting device using metal-organic chemical vapor deposition, comprising the steps of: a first layer lamination step of growing a first layer containing Al and In as a composition; a cap layer lamination step of growing a cap layer containing Ga as a composition on a surface of the first layer after the first layer lamination step; a second layer lamination step of growing a second layer containing at least one of Ga and In as a composition on a surface of the cap layer after the cap layer lamination step is performed; a hydrogen cleaning step of stopping the supply of source gas into the reactor after the cap layer lamination step and before the second layer lamination step, and supplying hydrogen into the reactor to clean at least the surface of the cap layer; Equipped with A method for manufacturing a nitride semiconductor light-emitting device, wherein the carrier gas in the second layer stacking step is only N 2 .

2. 2 . The method for manufacturing a nitride semiconductor light-emitting device according to claim 1 , wherein the hydrogen cleaning step comprises supplying hydrogen into the reactor to clean at least the surface of the cap layer, and then stopping the supply of hydrogen to the reactor.

3. A method for producing a nitride semiconductor light-emitting device using metal-organic chemical vapor deposition, comprising the steps of: a first layer lamination step of growing a first layer containing Al and In as a composition; a cap layer lamination step of growing a cap layer containing Ga as a composition on a surface of the first layer after the first layer lamination step; a second layer lamination step of growing a second layer containing at least one of Ga and In as a composition on a surface of the cap layer after the cap layer lamination step is performed; a hydrogen cleaning step of stopping the supply of source gas into the reactor after the cap layer lamination step and before the second layer lamination step, and supplying hydrogen into the reactor to clean at least the surface of the cap layer; Equipped with The method for manufacturing a nitride semiconductor light-emitting device, wherein the cap layer has a thickness in a stacking direction of 0.3 nm or more and 5 nm or less.

4. A method for producing a nitride semiconductor light-emitting device using metal-organic chemical vapor deposition, comprising the steps of: a first layer lamination step of growing a first layer containing Al and In as a composition; a cap layer lamination step of growing a cap layer containing Ga as a composition on a surface of the first layer after the first layer lamination step; a second layer lamination step of growing a second layer containing at least one of Ga and In as a composition on a surface of the cap layer after the cap layer lamination step is performed; a hydrogen cleaning step of stopping the supply of source gas into the reactor after the cap layer lamination step and before the second layer lamination step, and supplying hydrogen into the reactor to clean at least the surface of the cap layer; Equipped with A method for manufacturing a nitride semiconductor light-emitting element, wherein the numerical value A of Equation 1 is determined by the flow rate F1 [slm] of hydrogen supplied into the reactor in the hydrogen cleaning step, the supply time T [min] for supplying hydrogen into the reactor in the hydrogen cleaning step, and the flow rate F2 [slm] of ammonia supplied into the reactor in the hydrogen cleaning step, and is 20 or more and 80 or less. A = (F1 x T) / F2 ... Equation 1

5. A method for manufacturing a nitride semiconductor light-emitting device using metal-organic chemical vapor deposition, comprising the steps of: a first layer lamination step of growing a first layer containing Al and In as a composition; a cap layer lamination step of growing a cap layer containing Ga as a composition on a surface of the first layer after the first layer lamination step; a second layer lamination step of growing a second layer containing at least one of Ga and In as a composition on a surface of the cap layer after the cap layer lamination step is performed; a hydrogen cleaning step of stopping the supply of source gas into the reactor after the cap layer lamination step and before the second layer lamination step, and supplying hydrogen into the reactor to clean at least the surface of the cap layer; Equipped with A method for manufacturing a nitride semiconductor light-emitting device, wherein a growth temperature in the second layer stacking step is equal to or lower than a growth temperature in the first layer stacking step.

6. A first layer containing Al and In in its composition; a cap layer including Ga as a composition and laminated on a surface of the first layer; a second layer that is stacked on a surface of the cap layer and contains at least one of Ga and In; Equipped with a band gap in the cap layer is smaller than a band gap in the first layer and the second layer adjacent to the cap layer; The nitride semiconductor light emitting device, wherein the cap layer has a thickness in a stacking direction of 0.3 nm or more and 5 nm or less.

7. A first layer containing Al and In in its composition; a cap layer including Ga as a composition and laminated on a surface of the first layer; a second layer that is stacked on a surface of the cap layer and contains at least one of Ga and In; Equipped with a band gap in the cap layer is smaller than a band gap in the first layer and the second layer adjacent to the cap layer; The surface concentration of Ga in the cap layer is 2.5×10 14 cm -2 Above and 4.1 x 10 15 cm -2 A nitride semiconductor light-emitting device as described below.